How to increase brand value expanding the category and brand presence to the main meal occasion for Sumol- Compal - Vieira, Antonio (2019)
Having registered negative retail value growth of 4% in Portugal in 2014, the juice category is set to decline further by 5,5% until 2019. Manufacturers of juices and nectars are therefore increasingly looking for new categories in order to balance this negative forecast in their home territory. One apparent growth opportunity for Compal, the leading producer of juices and nectars, is to expand its commercial reach to new occasions of consumption. This report carefully analyzes the opportunities related to an expansion to the main meal occasion and introduces a complete marketing and communications plan for a possible new main meal juice, Compal à Mesa. The product concept represents a rather premium positioning for the main meal occasion, including new flavor mixes that are targeted at different occasions of meals. The justification of the introduced concept includes a discussion of the primary and secondary research that was performed